Developments in quantitative dimensional synthesis (1970-present): four-bar motion generation. Issue 1 (2nd January 2018) - Lee, Wen-Tzong; Russell, Kevin
Abstract: Dimensional synthesis is a type of inverse problem in linkage kinematics where the objective is to calculate the linkage dimensions required to achieve prescribed linkage output motion. Motion generation is a particular category of dimensional synthesis where the objective is to calculate the linkage dimensions required to achieve a group of prescribed link positions. In motion generation for a four - bar linkage, positions are prescribed for the coupler link. While early motion generation methods were primarily qualitative, ongoing advancements in computing hardware and software continue to make quantitative motion generation more practical. By providing overviews of works representative of developments in quantitative four-bar motion generation since 1970, this work is essentially an overview that spans over 40 years of developments in quantitative four-bar motion generation.